Hubungan Pola Asuh Orang Tua Otoriter dengan Kemandirian Anak Usia Pra Sekolah - Zulfa Okta Asnida; Apsa Madantia (STIKes Patria Husada Blitar in collaboration with PPNI Kabupaten blitar, 2014)
One of the roles of the parents is to make the children independent, which means increasing the children's ability in fulfilling their needs or with a little help from the others. In general, as common knowledge, parents usually use authoritarian parenting in raising their children. The purpose of this study was to determine the correlation of parents using authoritarian parenting way with the independent of 3- 5 years old preschool children. Method: The research designed using cross sectional analytical correlation. The subject of this research was all of the parents who have 3-5 years old preschool children in Berlian Desa Bendorejo District of Udanawu  collected by total sampling technique and analized using chi square technic Result: The results of this research showed that respondents with authoritarian parenting way tend to have children with low self-reliance of 38.9 %. Meanwhile, respondents with non- authoritarian parenting way tend to have children with high self-sufficiency of 38.9 % . The results of Chi-square test showed p value = 0.025 . From the data analysis it was obtained the value of the significance level was 0.025. Discussion: Based on these results it could be concluded that there was a correlation between of parents using authoritarian parenting way with the independent of 3-5 years old preschool children. It was expected that the respondents provided appropriate parenting way for the children in developing their independent.